Capacity building of farmers in developing fresh flower business in Berjo Village, Ngargoyoso District - Suminah Suminah; Padmaningrum Dwiningtyas; Anantanyu Sapja; Kristiyanto Agus (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Fresh flowers potentially become an alternative business for Berjo farmers, Karanganyar District. Berjo Flora is of a farmer group that engages in the fresh flowers business, but the venture still has some obstacles such as cultivation skills, business diversification, business management, marketing, and business motivation. Therefore, this Program Kemitraan Masyarakat (PKM) is undertaken as an effort to solve the problem in the form of; (1) chrysanthemum flower cultivation training; (2) business motivation, management, and online marketing; (3) flower bouquet training. Partners in this program consist of 14 members of Berjo Flora farmer group that are active as fresh flowers farmers. Results of this effort are: (1) improved business motivation and skills of the fresh flowers farmers; (2) establishment of marketing network and information exchange between fresh flower farmer communities.